Chiral recognition of some D and L-amino acids by microcrystalline cellulose assisted diffusion-ordered NMR spectroscopy - Bowen Han; Jing He; Shaohua Huang (Journal of Magnetic Resonance Open)
Chiral amino acids play an indispensable role in living organisms. Diffusion-ordered NMR spectroscopy is an effective NMR tool and a noninvasive analytical method for the analyses of mixture without the need for physical separation of the analytes. However, conventional diffusion-ordered NMR spectroscopy method usually fails to resolve the mixtures of chiral amino acids because of their same molecular masses, sizes, and shapes. Microcrystalline cellulose has been gradually gained more and more interest owing to its wide compatibility, surface area, excellent separation efficiency, non-toxicity, cost-effective, and mechanical stability in many fields. Herein we provide a fast, simple, specific and sensitive method to resolve some D and L-amino acids mixtures by using microcrystalline cellulose as a matrix. This work recognized some D and L- proteinogenic amino acid enantiomers with diffusion-ordered NMR for the first time.